The Dynamics of the Constitutional Court’s Authority in Determining Age Limit Requirements for Political Leadership Candidates - Rahmad Prasetyo; Richard (Yayasan Cendekia Gagayunan Indonesia, 2025)
The Constitutional Court of Indonesia plays a central role in the national constitutional system through its authority to review statutory laws against the 1945 Constitution of the Republic of Indonesia, and one of the most debated constitutional issues in recent years concerns the Court’s authority to interpret and determine age limit requirements for political leadership candidates, particularly presidential and regional head candidates. Although such age requirements were originally regulated explicitly by statutory provisions, Constitutional Court decisions have significantly altered these norms, generating legal and political controversy and affecting the structure of Indonesia’s electoral system. This study aims to analyze the dynamics of the Constitutional Court’s authority in adjudicating cases related to age limit requirements for political leadership candidates and to examine the constitutional and democratic implications of these decisions. Employing a normative legal research method with a statute approach and a case approach focusing primarily on Constitutional Court Decision No. 90/PUU-XXI/2023—this study relies on primary legal materials such as the 1945 Constitution, election and regional governance statutes, and Constitutional Court rulings, as well as secondary materials from academic journals, books, and recent scholarly literature. The findings indicate that the Constitutional Court, in this decision, has gone beyond its traditional role as a negative legislator and has assumed characteristics of a positive legislator by effectively creating new legal norms through progressive constitutional interpretation, thereby raising concerns regarding the limits of judicial authority, the potential shift of legislative functions from the legislature to the judiciary, and the need to reinforce institutional checks and balances to maintain legal certainty and democratic legitimacy within Indonesia’s constitutional and electoral system.